From country to nation : ethnographic studies, kokugaku, and spirits in nineteenth-century Japan - Fujiwara, Gideon (Cornell East Asia series, 2021)
"This book tracks the emergence of the modern Japanese nation in the nineteenth century through the history of some of its local aspirants. It explores how kokugaku (Japan studies) scholars envisioned their place within Japan and the globe, while living in a castle town and domain far north of the political capital"--